PENGARUH BELANJA MODAL, BELANJA BARANG DAN JASA, DAN BELANJA TAK TERDUGA TERHADAP PENYERAPAN ANGGARAN PADA PEMERINTAH KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN - Desir Rohma Dyna; Nelly Masnila; Riza Wahyudi (Gapenas Publisher, 2023)
The purpose of this research is to find out the effect of capital expenditures, good and services expenditures, and unexpected expenditures on budget absorption at the government of the district/city in South Sumatera Province. The population in this research are all district/cities in South Sumatera Province which is includes 17 district/cities with saturated sampling, the population were used as sample so the sample of this research was 17 district/cities in South Sumatera. The data used in this research is secondary data obtained from the website of the Audit Board of Republik Indonesia with an observation year of 5 years. The analysis data method used in this research was multiple regression analysis method. Based on the results of data processing through the IBM SPSS Statistic Software that had been analyzed, it is concluded that the capital expenditures, good and services expenditures affect budget absorption and unexpected expenditures did not affect budget absorption at the Government of the District/City in South Sumatera Province